2014
DOI: 10.1039/c4tc01572j
|View full text |Cite
|
Sign up to set email alerts
|

CaY2Si2S8:Ce3+: a novel green-emitting thiosilicate phosphor for white light-emitting diodes

Abstract: The luminescence of a green-emitting CaY2Si2S8:Ce3+ phosphor and its applicability in fabrication of white LEDs with high CRI and varied CCTs were explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…[25][26][27][28][29][30] In general, phosphors are vital to the development of the WLED lighting and backlight display industry. 39,[41][42][43][44][45][46][47] The emphasis was also be placed on the relationships among crystal structures, luminescence properties, and device performances. Therefore, novel and acceptable fluorescent materials for improving the performances of solid-state lighting must be developed.…”
Section: Jun Linmentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27][28][29][30] In general, phosphors are vital to the development of the WLED lighting and backlight display industry. 39,[41][42][43][44][45][46][47] The emphasis was also be placed on the relationships among crystal structures, luminescence properties, and device performances. Therefore, novel and acceptable fluorescent materials for improving the performances of solid-state lighting must be developed.…”
Section: Jun Linmentioning
confidence: 99%
“…[58][59][60][61][62][63][64][65][66][67][68][69] Commonly, the nephelauxetic effect is linked to the covalency of the crystal. [41][42][43][44][45][46][47]93,95 If the activator ions were surrounded by anion groups, the higher charge density on the anion groups would exert the stronger nephelauxetic effect on activator ions. Thus the covalency of the crystal is related to the electronegativity of anions and the cation-anion distance.…”
Section: Anionic Substitutionmentioning
confidence: 99%
“…To determine the dependable approximation of the actual crystal structure for SLSSC, the isomorphic structure data of La 2 PbSi 2 S 8 was adopted as the starting model. This model was also adopted by the previous study for determining the structure of similar thiosilicate BaLa 2 Si 2 S 8 and CaY 2 Si 2 S 8 . The Rietveld refinements were carried out for the host SrLa 2 Si 2 S 8 (SLSS) and the doping sample (5 mol%) SL 1.9 SSC 0.1 from the XRD data, which indicated that the target structure (crystallize into hexagonally with space group R3c (No.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the energy transfer mechanism between the sensitizer (Eu 2+ ) to activator (Mn 4+ ) ions and the relation can be revealed by the Dexter's energy transfer theory: [36][37][38]…”
Section: Resultsmentioning
confidence: 99%